EFFECT OF INFORMATION SHARING ON SUPPLY CHAIN PERFORMANCE MEDIATED BY COMPANY RELATIONSHIP (Study at Batik SMEs in Yogyakarta City) - Titik Kusmantini; Dika Setya Prayogi; Tri Wahyuningsih; Krisnandini Wahyu Pratiwi (Universitas Lambung Mangkurat, 2020)
Entering the era of globalization, economic shifts and market trends are increasingly fast and difficult to predict, so the role of information as the main ingredient of decision making in companies becomes important. This study aims to determine the effect of information sharing (IS) on supply chain performance (SCP) which is mediated by the company relationship (CR). The survey was conducted through distributing questionnaires to 48 samples of batik SMEs in Yogyakarta city selected by simple random sampling method then the data was analyzed using path analysis with SPSS 15. The results of the study found a significant positive effect of IS on SCP indicated by the correlation coefficient (R) of 0.374 and t count> t table at a significance level of 5% (4,976> 2,014). Then the significant positive effect of IS on CR is shown by the value of the correlation coefficient (R) of 0.453 and the value of t count> t table at the significance level of 5% (4.540> 2.014). Then the significant positive effect of CR on SCP is shown by the value of the correlation coefficient (R) of 0.360 and the value of t count> t table at the significance level of 5% (3.896> 2.014). Finally, the significant positive effect of IS on the SCP that is mediated by CR is shown by the sum of the coefficients of 0.537 then tested using the sobel test and produces z count> t table at a significance level of 5% (3.078> 2.014). This research contributes to the development and theoretical application, especially in the field of operational management.